Key factors controlling the accumulation of oil reservoir in the Gaosheng area of Western Depression, Liaohe Basin, Northeastern China - Zhao, Guangjie; Jiang, Fujie; Zhang, Qiang; Pang, Hong; Liu, Xingzhou; Chen, Di (Frontiers in Earth Science, 2024)
The Proterozoic oil in Gaosheng area of the Western Depression of Liaohe Basin has great potential and is an important exploration field. However, the study about control factors of Gaosheng reservoir needs to be improved. The source rocks are characterized by using geochemical techniques and the structural evolution history is restored by using 2D-Move software. The characteristics of reservoirs and caps are clarified, and the controlling factors of reservoir formation are summarized. The oil generation intensity of Es4 and Es3 is generally 5×10 6 -10×10 6 t/km 2 , indicating that the oil source is sufficient. The sandstone reservoir has fracture and dissolution porosity, which provide storage space for oil accumulation. Faults and unconformities provide pathways for oil migration. The dense Fangshenpao and Mesozoic basalt is a good cap layer to preserve the reservoir, which effectively prevents the upward migration of oil. According to the comprehensive analysis of main controlling factors, the favorable exploration areas are pointed out. The research results are of great significance to guide the future oil and gas exploration in Liaohe Basin.